Corticosteroid injection in shoulder impingement. (July 2015) - Bashir, Fouzia; Wong, Way Main; Innes, Sue
<x content-type="archive" xml:space="preserve">Abstract</x> Study design Case report. Objective To evaluate the effectiveness of steroid injection in shoulder impingement syndrome. Case presentation A 40-year-old man presented with right shoulder subacromial pain who did not improve with physiotherapy. However, the patient showed improvement in pain (numerical pain rating scale from 8 to 0) and shoulder functions (the shoulder pain and disability index fell from 49 to 4%) with corticosteroid injection. Discussion and conclusions The steroid injection is an effective intervention and blind injection technique was accurate and produced good outcome in this patient. The outcome of this case correlates with research evidence which supports the effectiveness of steroid injections for pain relief in shoulder impingement syndromes. The effectiveness of the blind injection technique used also correlates with other studies in the literature.